The SUS that we are building: knowledge and performance of different social actors (Research, Society and Development, 2020)
The Brazilian Federal Constitution, in 1988, establishes the Unified Health System (SUS), the result of the struggle for redemocratization in the country and movement for Sanitary Reform that occurred in the 80's. From this perspective, this study was dedicated to understanding the knowledge and different social actors in the construction of SUS. This is a cross-sectional study with a qualitative approach, conducted with workers of Primary Health Care units of a city in the interior of São Paulo. Data collection took place in the second semester of 2019, with the signature of the consent form, through interviews with an instrument prepared by the authors. Data were subjected to thematic content analysis. Eight workers (87.0%), nursing assistants (50%), and working time at SUS between one and 15 years participated. Three categories were elaborated: 1. Primary care workers' knowledge about SUS principles; 2. The workers and the doctrinal principles of the SUS; 3. Primary care workers' knowledge about SUS organizational principles. It was easily observed the lack of knowledge about SUS by SUS workers. It is worrying because, when thinking about improving the quality of health care, the principles and guidelines of SUS should be the basis for this. Continuing and continuing education actions should be promoted to clarify the basic principles and guidelines, which was the basis of this research and the greatest lack of knowledge presented by workers, as well as elucidation of routine work actions.